Characterization of wide bandgap power semiconductor devices - Wang, Fei (Fred); Zhang, Zheyu; Jones, Edward A. (IET energy engineering series ;, 2018)
This book is an authoritative overview of Wide Bandgap (WBG) device characterization providing essential tools to assist the reader in performing both static and dynamic characterization of WBG devices, particularly those based on using silicon carbide (SiC) and gallium nitride (GaN) power semiconductors.